c(3)G encodes a Drosophila synaptonemal complex protein - Page, Scott L. (Cold Spring Harbor Laboratory Press, 2001)
The meiotic mutant c(3)G (crossover suppressor on 3 of Gowen) abolishes both synaptonemal complex (SC) formation and meiotic recombination, whereas mutations in the mei-W68 and mei-P22 genes prevent recombination but allow normal SC to form. These data, as well as a century of cytogenetic studies, support the argument that meiotic recombination between homologous chromosomes in Drosophila females requires synapsis and SC formation. We have cloned the c(3)G gene and shown that it encodes a protein that is structurally similar to SC proteins from yeast and mammals. Immunolocalization of the C(3)G protein, as well as the analysis of a C(3)G-eGFP expression construct, reveals that C(3)G is present in a thread-like pattern along the lengths of chromosomes in meiotic prophase, consistent with a role as an SC protein present on meiotic bivalents. The availability of a marker for SC in Drosophila allowed the investigation of the extent of synapsis in exchange-defective mutants. These studies indicate that SC formation is impaired in certain meiotic mutants and that the synaptic defect correlates with the exchange defects. Moreover, the observation of interference among the residual exchanges in these mutant oocytes implies that complete SC formation is not required for crossover interference in Drosophila.